2008
DOI: 10.1007/s10577-008-1198-6
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome pairing in allotetraploid hybrids of Festuca pratensis × Lolium perenne revealed by genomic in situ hybridization (GISH)

Abstract: Genomic in situ hybridization (GISH) was used to make a detailed study of chromosome pairing at metaphase I (MI) of meiosis in six F(1) hybrid plants of the allotetraploid Festuca pratensis x Lolium perenne (2n = 4x = 28; genomic constitution FpFpLpLp). The mean chromosome configurations for all hybrids analysed were 1.13 univalents + 11.51 bivalents + 0.32 trivalents + 0.72 quadrivalents, and the mean chiasma frequency was 21.96 per cell. GISH showed that pairing was predominantly intragenomic, with mean numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 40 publications
0
28
0
2
Order By: Relevance
“…Similarly, a 9: 1 ratio of homologous vs. homoeologous pairing was detected in tetraploid F1 F. pratensis ! L. perenne hybrids (Zwierzykowski et al, 2008). An even lower frequency of homoeologous association (14: 1 ratio of homologous vs. homoeologous pairing) was reported in our previous study in tetraploid F1 L. multiflorum !…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 9: 1 ratio of homologous vs. homoeologous pairing was detected in tetraploid F1 F. pratensis ! L. perenne hybrids (Zwierzykowski et al, 2008). An even lower frequency of homoeologous association (14: 1 ratio of homologous vs. homoeologous pairing) was reported in our previous study in tetraploid F1 L. multiflorum !…”
Section: Discussionmentioning
confidence: 99%
“…Meadow fescue (Festuca pratensis Huds., Fp), a species closely related to Lp, has lower nutritive value but is one of the most winter-hardy species within the Lolium-Festuca complex (Humphreys, 1989). The transfer of the genes governing winter-hardiness (WH) from Fp to Lp is achievable, as both species hybridize readily and their homologous chromosomes pair and recombine at high frequency during meiosis (Zwierzykowski et al, 2008). However, not all the physiological bases of WH, expressed differently in Fp and Lp, have been identified and comprehensive research is still required to dissect this complex trait.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency was 21.96 chiasmata per cell. GISH showed that the pairing was predominantly intragenomic (Zwierzykowski et al, 2008).…”
Section: Use Of Gish For Meiotic Analysis In Hybridsmentioning
confidence: 99%